2016
DOI: 10.11648/j.ajce.20160402.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Design Ductility on the Progressive Collapse Potential of RC Frame Structures Designed to Eurocode 8

Abstract: Abstract:Progressive collapse is the cause of most structural failures around the world. The US General Service Administration (GSA) has presented guidelines for the assessment of the vulnerability of building structures to progressive collapse. It has been established in literature that the philosophy of ductility and redundancy used in seismic design is beneficial in resisting progressive collapse but not accounted for in these guidelines. The GSA methodology is particularly suited to seismic codes which all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…By comparing maximum load factors, it was observed that the resistance of the structure to collapse is lowest when a corner column is lost (Case 3) since it has the lowest load factors and ductilities. The conclusion of the corner column loss case being the most critical is consistent with the findings of [17], [18] and [19] who all showed that reinforced concrete buildings were most vulnerable to progressive collapse when a corner column is lost. 25 is the only model found vulnerable to progressive collapse in all these cases because the GSA methodology prescribes a maximum load factor of 2.0 to assure resilience to progressive collapse.…”
Section: Effect Of Removed Column Locationsupporting
confidence: 89%
“…By comparing maximum load factors, it was observed that the resistance of the structure to collapse is lowest when a corner column is lost (Case 3) since it has the lowest load factors and ductilities. The conclusion of the corner column loss case being the most critical is consistent with the findings of [17], [18] and [19] who all showed that reinforced concrete buildings were most vulnerable to progressive collapse when a corner column is lost. 25 is the only model found vulnerable to progressive collapse in all these cases because the GSA methodology prescribes a maximum load factor of 2.0 to assure resilience to progressive collapse.…”
Section: Effect Of Removed Column Locationsupporting
confidence: 89%
“…A certain similarity can be observed between numerical procedures for the analysis of progressive collapse, and the analysis of structures exposed to earthquake action. The influence of the structure's ductility on progressive collapse of the system is investigated in [87], because [15] excludes ductility and residual bearing capacities, which is used in seismic design. The corresponding regulations can be used to reduce the likelihood of PC.…”
Section: Introduction and Literature Overviewmentioning
confidence: 99%